KELAYAKAN MEDIA PEMBELAJARAN FOCUSKY TERINTEGRASI NILAI AGAMA UNTUK MENGEMBANGKAN KARAKTER DISIPLIN - Irma Yunita; Retno Triwoelandari; Fakhri Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
The purpose of this study was to determine the feasibility of integrated focusky learning media of religious value to develop the discipline character of elementary school students. The method used in this research is research and development or Research and Development (R & D) which consists of three stages, namely: 1) preliminary study, 2) model development, 3) model testing. This learning media is assessed by three experts. The expert consists of material, language and media experts. Data collection techniques use media questionnaires, lattice instruments for student assessment of products, character achievement instruments. Analysis of data using SPSS 20 for Windows using paired samples t-test and t test independent samples t-test. The sample used is grade 5 elementary school students. Results obtained by material experts with a percentage of feasibility of 84% with very valid categories, linguists with a feasibility percentage of 77% with valid categories, media expert assessment results of 93% with very valid categories and learning media are valued by students as support. The average results of differences in pretest and posttest in the experimental class get a value of 7.56250 and the control class gets the average difference in pretest and posttest of 4.35714. This shows that focusky media integrated religious values are worthy of being used in the learning process and can develop the character of student discipline.